A specific plasma lipid signature associated with high triglycerides and low HDL cholesterol identifies residual CAD risk in patients with chronic coronary syndrome. (December 2021) - Di Giorgi, Nicoletta; Michelucci, Elena; Smit, Jeff M.; Scholte, Arthur J.H.A.; El Mahdiui, Mohammed; Knuuti, Juhani; Buechel, Ronny R.; Teresinska, Anna; Pizzi, Maria N.; Roque, Albert; Poddighe, Rosa; Parodi, Oberdan; et al.
Abstract: Background and aims: Elevated triglycerides (TG) and low high-density lipoprotein cholesterol (HDL-C) define a specific lipid profile associated with residual coronary artery disease (CAD) risk independently of total cholesterol and low-density lipoprotein cholesterol (LDL-C) levels. Aim of the present study was to assess whether TG/HDL-C ratio, coronary atherosclerosis and their change over time are characterized by a specific lipidomic profiling in stable patients with chronic coronary syndrome (CCS). Methods: TG/HDL-C ratio was calculated in 193 patients (57.8 ± 7.6 years, 115 males) with CCS characterized by clinical, bio-humoral profiles and cardiac imaging. Patient-specific plasma targeted lipidomics was defined through a high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) strategy. Patients underwent coronary computed tomography angiography (CTA) and an individual CTA risk score, combining extent, severity, composition, and location of plaques, was calculated. All patients entered a follow-up (6.39 ± 1.17 years), including clinical, lipidomics and coronary CTA assessments. Results: Patients were divided in groups according to baseline TG/HDL-C quartiles: IQ (<1.391), IIQ (1.392–2.000), IIIQ (2.001–3.286), and IVQ (≥3.287). A specific pattern of altered lipids, characterized by reduced plasma levels of cholesterol esters, phosphatidylcholines and sphingomyelins, was associated with higher TG/HDL-C both at baseline and follow-up (IVQ vs IQ). The CTA risk score increased over time and this lipid signature was also associated with higher CTA score at follow-up. Conclusions: In stable CCS, a specific lipidomic signature identifies those patients with higher TG/HDL- C ratio and higher CTA score over time, suggesting possible molecular pathways of residual CAD risk not tackled by current optimal medical treatments. Graphical abstract: Image 1 Highlights: Residual coronary artery disease risk is a relevant clinical unmet need. Residual risk is associated with specific cardiometabolic profiles. We analyzed plasma of 193 patients at baseline and follow-up. A common panel of lipid biomarkers identifies patients with cardiometabolic risk. These 13 lipids associated together with TG/HDL-C ratio and prognostic risk score.